2023
DOI: 10.1038/s41598-023-32629-x
|View full text |Cite
|
Sign up to set email alerts
|

Macular outer nuclear layer, ellipsoid zone and outer photoreceptor segment band thickness, axial length and other determinants

Abstract: The study aims to assess the thickness of the retinal outer nuclear layer (ONL), ellipsoid zone (EZ) and photoreceptor outer segment (POS) band in various macular regions and its associations with axial length and other parameters. Participants of the Beijing Eye Study 2011 underwent a series of examinations including spectral-domain optical coherence tomography of the macula. The current study included 2213 participants without retinal or optic nerve diseases (age: 61.7 ± 8.4 years; range 50–93 years); axial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Further analysis using an insulin microarray resulted that the levels of insulin and those related factors including IGF2, IGF-2R, IGF binding protein 1 (IGFBP-1), IGFBP-2, IGFBP-3, IGFBP-4 and IGFBP-6 were markedly increased in patients with pathogenic myopia as compared with the controls [ 59 ]. Alternatively, the multivariable analysis using 2213 participants without retinal or optic nerve diseases underwent a series of measurements including spectral-domain optical coherence tomography, which indicated that a thicker retinal outer nuclear layer was associated (correlation coefficient r: 0.40) with shorter axial length and shorter disc–fovea distance after adjusting for younger age, male sex (beta: 0.24; p < 0.001), lower serum cholesterol concentration (beta: −0.05; p = 0.04) and thicker subfoveal choroidal thickness [ 60 ]. Therefore, this collective evidence rationally supported not only that systemic glycemic regulation factors were indeed involved in the pathogenesis of myopia but also the current investigation suggesting that SREBP-related regulation of FA, TG and cholesterol synthesis may be one of the critical factors to induce AL elongation via HSSFs in myopic eyes.…”
Section: Discussionmentioning
confidence: 99%
“…Further analysis using an insulin microarray resulted that the levels of insulin and those related factors including IGF2, IGF-2R, IGF binding protein 1 (IGFBP-1), IGFBP-2, IGFBP-3, IGFBP-4 and IGFBP-6 were markedly increased in patients with pathogenic myopia as compared with the controls [ 59 ]. Alternatively, the multivariable analysis using 2213 participants without retinal or optic nerve diseases underwent a series of measurements including spectral-domain optical coherence tomography, which indicated that a thicker retinal outer nuclear layer was associated (correlation coefficient r: 0.40) with shorter axial length and shorter disc–fovea distance after adjusting for younger age, male sex (beta: 0.24; p < 0.001), lower serum cholesterol concentration (beta: −0.05; p = 0.04) and thicker subfoveal choroidal thickness [ 60 ]. Therefore, this collective evidence rationally supported not only that systemic glycemic regulation factors were indeed involved in the pathogenesis of myopia but also the current investigation suggesting that SREBP-related regulation of FA, TG and cholesterol synthesis may be one of the critical factors to induce AL elongation via HSSFs in myopic eyes.…”
Section: Discussionmentioning
confidence: 99%
“… 30 A second study correlated the average ISOS layer thickness of approximately 250 OCT scans, corrected for age and sex, with the average histological cone density data. 31 Correction for age and sex is important when matching against normative data, because it was found that cone density, 28 , 32 as well as OSL, 33 , 34 decrease with age, and RT depends on sex, with males tending to have a thicker retina. 35 , 36 This approach was, however, unable to consider individual differences in cone density, which are shown to be significant (see next paragraph).…”
Section: Discussionmentioning
confidence: 99%
“…The general structure of the human retina is shown schematically in Figure 1. Starting from the innermost layer that is closer to the anterior part of the face and the vitreous humor that fills the eye, the retina is composed of the inner limiting membrane (ILM), retinal nerve fiber layer (RNFL), retinal ganglion cell (RGC) layer, inner plexiform layer (IPL), inner nuclear layer (INL), outer plexiform layer (OPL), outer nuclear layer (ONL), outer limiting membrane (OLM), the ellipsoid zone (EZ), the photoreceptor outer segments (POSs), and the retinal pigment epithelium (RPE) [36]. As described by Masland et al (2012), each layer is composed of different cell types with unique functions relevant to different aspects of vision [1].…”
Section: The Retina 21 Retinal Structure and Information Processingmentioning
confidence: 99%